Geomorphological Approach to Cliff Instability in Volcanic Slopes: A Case Study from the Gulf of Naples (Southern Italy) - Giuseppe Di Crescenzo; Nicoletta Santangelo; Antonio Santo; Ettore Valente (Geosciences, 2021)
This paper deals with the problem of cliff stability and proposes a geomorphological zonation of a cliff using a sector of the Posillipo promontory (named the Coroglio-Trentaremi sea cliff, Italy), in the Campi Flegrei coastal area, as a case study. A detailed geological and geomorphological analysis was carried out, by combining field work with analysis of detailed scale topographic maps, orthophoto, and stratigraphical data from deep boreholes. Field and borehole data, together with structural data collected in seven different stations along the cliff, allowed us to derive six geological cross-sections and to reconstruct the complex stratigraphical and structural setting of the cliff. Geomorphological analysis focused on the detection of the main geomorphological factors predisposing to cliff instability. We selected the most significant factors and divided them into two groups: factors influencing landslide intensity and factors influencing cliff instability. Then, by means of a heuristic approach, we constructed a matrix that was used to derive a map showing the geomorphological zonation of the sea cliff. This map may enable to development of a reliable scenario of cliff instability and consequent retreat, which may be useful either to plan intervention works in the most critical areas or to organize prevention plans aimed at risk mitigation.